The neutrophil migration induced by tumour necrosis factor alpha in mice is unaffected by glucocorticoids - C. A. Cecilio; E. H. Costa; P. Ucelli; C. A. A. Chaves; M. C. Toffoli; C. A. Flores; F. Q. Cunha; S. H. Ferreira; W. M. S. C. Tamashiro (Hindawi Limited, 1997)
Macrophages harvested from the peritoneal cavities of rats release a neutrophil chemotactic factor (MNCF) in response to stimulation with Gram-negative bacterial lipopolysaccharide (LPS). MNCF has been shown to be active in rats treated with dexamethasone, a glucocorticoid that usually inhibits the neutrophil migration induced in this species by interleukin (IL)-1, tumour necrosis factor alpha (TNFα), IL-8, C5a and leukotriene B4 (LTB4). Here we report that macrophages harvested from peritoneal cavities of mice, and stimulated in vitro with LPS, also release a factor that induces neutrophil migration in dexamethasone-treated animals. This chemotactic activity was neutralized by the incubation of the LPS-stimulated macrophage supernatants with a purified polyclonal IgG anti-mouse TNFα. In addition, significant amounts of TNF were detected in the supernatants. The neutrophil migration induced by intraperitoneal administration of recombinant murine TNFα was also unaffected by pretreatment of the mice with dexamethasone. Moreover, neutrophil migration induced by intraperitoneal injection of LPS was completely blocked by pretreatment of the mice with a monoclonal antibody against murine TNFα. In conclusion, our results support the hypothesis that, in contrast to the role of TNF in rats (where it indirectly induces neutrophil migration), in mice, it may be an important mediator in the recruitment of neutrophils to inflammatory sites.